Evaluation of Choroidal Thickness in Patients with Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma - ARICI, MUSTAFA KEMAL; DURSUN, AYHAN; Ozec, Ayse Vural; Dogan, Oznur; DURSUN, Feyza Gulac; TOKER, MUSTAFA İLKER; TOPALKARA, AYŞEN; ARICI, MUSTAFA KEMAL; ERDOĞAN, HAYDAR (My University, 2016)
Purpose. To compare the macular and peripapillary choroidal thickness in eyes with pseudoexfoliation (PEX) syndrome and PEX glaucoma with the normal eyes of healthy controls. Materials and Methods. In this prospective study, 30 eyes of 30 patients with PEX syndrome, 28 eyes of 28 patients with PEX glaucoma, and 30 eyes of 30 age-matched healthy subjects were enrolled. Choroidal thicknesses in the macular and peripapillary areas were measured by using spectral domain optical coherence tomography. Results. Gender, age, and axial length did not significantly differ between the groups (all, p > 0.05). The mean values of choroidal thickness in the macular and peripapillary areas (except the superior quadrant) in the patients with PEX syndrome and PEX glaucoma were lower compared with controls (all p < 0.05). The mean values of the macular and peripapillary choroidal thickness in the PEX glaucoma group were lower compared with PEX syndrome group; however this difference was not significant. Conclusions. The findings of this study revealed that macular and peripapillary choroidal thicknesses were decreased in PEX syndrome and PEX glaucoma cases. The role of choroid in the development of glaucomatous damage in patients with PEX syndrome remains unclear.